Immunity as key factors that influence cognitive development on children - Oktarina, Molly Dumakuri; Sekartini, Rini; Wasito, Erika; Kartjito, Melissa Stephanie (Indonesian Nutrition Association, 2023)
Immune cells in the central nervous system (CNS) of the fetus are essential for normal neurodevelopment. Innate immunity-related molecules, including cytokines, toll-like receptors and complement family, are known to be expressed in the brain. Microglia, macrophage-like immune cells that reside in the brain and spinal cord, constitute 80% of all immune cells in the brain, making them the most abundant immune cell type. Acquired immunity-related molecules, such as major histocompatibility complex and antibody receptor, are also known to be expressed in the brain. In addition to this, research has demonstrated that they play important functions in the development of the brain. Neurodevelopmental diseases, including schizophrenia, autism spectrum disorders, autism-like obsessive-compulsive behaviours and social impairment, are characterized by a disruption of a wide variety of processes in the developing brain that depend on the normal function of microglia. Enteric infections and malnutrition in the first two years of life are linked to later cognitive impairment. Multiple studies have shown that bacterial and viral illnesses have direct or indirect impacts on cognitive performance in children. The immune system is in constant communication with the central nervous system and participates in the control of behaviour and a range of other essential neurological activities throughout the lifespan.